2015
DOI: 10.3109/13880209.2014.970288
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipoic acid on acrylamide-induced neuropathy in rats with reference to biochemical, hematological, and behavioral alterations

Abstract: Context: Acrylamide (ACR) is a well-known neurotoxicant and carcinogenic agent which poses a greater risk for human and animal health. Objective: The present study evaluates the beneficial effects of a-lipoic acid (LA) on ACR-induced neuropathy. Materials and methods: A total of 40 male rats were divided into four groups: a placebo group; LA-treated group, administered orally 1% (w/w) LA mixed with diet; ACR-treated group, given 0.05% (w/v) ACR dissolved in drinking water; and LA + ACR-treated group, given LA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…Our study found that the level of thiobarbituric acid reactive products had increased significantly in liver, kidney and brain after administrated with AA due to the failure to detoxify the AA. Similar results noted by many researchers [8,14,32].…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that the level of thiobarbituric acid reactive products had increased significantly in liver, kidney and brain after administrated with AA due to the failure to detoxify the AA. Similar results noted by many researchers [8,14,32].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results noted by indicates many researchers. [23][24][25] A induced toxicity may be due to depletion in antioxidant enzymes as observed in present study which indicates loss of free radical scavenging activity. A exposure significantly inhibited the antioxidant enzymatic activities CAT and SOD levels in liver, kidney and brain.…”
Section: Discussionsupporting
confidence: 65%
“…ACR is well-known neurotoxicant that induced several biochemical, hematological, and behavioral alterations experimental animals (Lebda et al, 2015). Several efforts have been made to reduce the negative effects of acrylamide in foods by reducing acrylamide formation during food processing and/or by using certain food additives (Krishnakumar and Visvanathan, 2014;Lebda et al, 2015). Therefore, the present study was designed to investigate the ameliorative effect of chitosanstabilized SeNPs on hepatotoxicity of acrylamide in the experimental albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated the intensive presence of acrylamide (ACR) in foods exposed to high temperatures, particularly starchy foods such as potatoes, cereals and bakery products (Riboldi et al, 2014;Surdyk et al, 2004;Tareke et al, 2002). ACR is well-known neurotoxicant that induced several biochemical, hematological, and behavioral alterations experimental animals (Lebda et al, 2015). Several efforts have been made to reduce the negative effects of acrylamide in foods by reducing acrylamide formation during food processing and/or by using certain food additives (Krishnakumar and Visvanathan, 2014;Lebda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%